2021
DOI: 10.1177/2049463721992091
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the methods and drugs used for performing suprascapular nerve block injections for the non-surgical management of chronic shoulder pain

Abstract: Suprascapular nerve block (SSNB) injections are growing in popularity as a treatment option for people with chronic shoulder pain. The optimal method of injection and aftercare is unknown. This review describes the current methods and drugs used for performing SSNB injections in the non-surgical management of adults with chronic shoulder pain in order to inform future research in this area. Systematic searches of CINAHL, MEDLINE (OVID), AMED, Embase databases and the Cochrane Library were undertaken from incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…In this framework, we treated our patients with type I collagen through indirect ultrasound-guided injections (IUSGIs) [30,31]. Our results demonstrated that all patients received a large benefit after treatment with porcine type I collagen, thanks to its advantages such as high biocompatibility, the ability to facilitate reductions in pain and the ability to improve mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework, we treated our patients with type I collagen through indirect ultrasound-guided injections (IUSGIs) [30,31]. Our results demonstrated that all patients received a large benefit after treatment with porcine type I collagen, thanks to its advantages such as high biocompatibility, the ability to facilitate reductions in pain and the ability to improve mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The in situ collagen medical device, applied via indirect ultrasound guidance, has been shown to be a safe and effective approach in improving pain and function in a patient with symptomatic Morton's neuroma. At the same time, procedure IUSGI could constitute a good alternative approach in consideration of the simplicity, time consumption and safety of execution compared to direct USG injection (DUSGI), reducing the procedure execution time, possible infectious adverse events and time-consuming patient management (IUSGI vs. DUSGI) [30,31]. Furthermore, the reduced physiological space associated with the MN becomes a safe and easily accessible point for the IUSGI procedure in order to correctly position the collagen in the target site.…”
Section: Discussionmentioning
confidence: 99%